An index for renal outcome in ANCA-associated glomerulonephritis - Vergunst, Clarissa; van Gurp, Eveline; Hagen, E. Christiaan; van Houwelingen, Hans C.; Hauer, Herbert A.; Noël, Laure-Hélène; Waldherr, Rüdiger; Ferrario, Franco; Woude, Fokko J. van der; Bruijn, Jan A.; Bajema, Ingeborg M. (American journal of kidney diseases, 2003)
BACKGROUND: The aim of this study is to analyze the predictive value of clinical, serological, and histological parameters for renal outcome in antineutrophil cytoplasmic autoantibody (ANCA)-associated glomerulonephritis by multivariate analysis and create an index valid for clinical use. METHODS: Data from 160 patients with Wegener's granulomatosis, microscopic polyangiitis, and idiopathic rapidly progressive glomerulonephritis without immune deposits (renal-limited vasculitis) were collected. The Cockcroft formula was used to assess renal function expressed by glomerular filtration rate (GFR) at the time of renal biopsy (t = 0) and 1 year later (t = 1). Other clinical parameters were age, sex, and diagnosis. ANCA test results were scored as cytoplasmic ANCA/antiproteinase 3 (anti-PR3) or perinuclear ANCA/antimyeloperoxidase (anti-MPO) positive or negative. Histological data included normal glomeruli, fibrinoid necrosis, extracapillary proliferation, granulomas, interstitial edema, focal and diffuse infiltrates, fibrosis, tubular cylinders/casts, tubular atrophy, tubular necrosis, sclerosis, mesangial proliferation, mesangial matrix expansion, arteriosclerosis, and infiltrates in arterioles. In a separate analysis, we explored whether there were histological differences between patients with anti-PR3 and anti-MPO ANCA test results. RESULTS: Forty percent of the variation in renal function at the time of biopsy can be explained by the presence or absence of tubular atrophy, normal glomeruli, fibrinoid necrosis, extracapillary proliferation, and age. Renal function at the time of biopsy is the best predictor for renal function at t = 1 in patients with ANCA-associated glomerulonephritis. Together with normal glomeruli, fibrinoid necrosis, and age, it explains more than 60% of the variation in GFR at t = 1. ANCA subtype has no independent contribution in predicting patient prognosis. Results translated into a clinically relevant index: GFR at t = 1 = 36.96 + 0.65* (GFR at t = 0) + 10.52 (if normal glomeruli present) + 7.72 (if fibrinoid necrosis present) - 0.42* (age). CONCLUSION: The index created with results from this study provides an indication of renal outcome in patients diagnosed with ANCA-associated glomerulonephritis.
Elektronische Reproduktion der Druckausgabe, 21 February 2008
Gesehen am 30.09.2022